PENERAPAN BYL’s GDLC PADA PERANCANGAN APLIKASI GAME EDUKASI PENGENALAN HEWAN: GAME EDUKASI PENGENALAN HEWAN - AZIS, ABDUL; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2022)
Computer technology has a positive impact at this time, especially in the world of education, one example is interactive learning using audio visuals, known as educational games. In designing educational games using SDLC, then there is an update that is devoted to game design, namely GDLC which was discovered by BYL's. In designing games using the BYL's GDLC method in making this educational game the theme of animal recognition, which before being made learning media contained in animal recognition learning books was less attractive to students, so that students were more interested in the process of learning animal recognition, educational games were made to attract interest. learning among students. In designing educational games using Adobe Flach CS6 software as the main media in its manufacture. Because Adobe Flash CS6 software is still widely used in making interactive educational games whose output can be used on Android and desktop.